Pengaruh Fundamental dan Makro Ekonomi Terhadap Harga Saham Perusahaan Multi Nasional (Studi Kasus Perusahaan Industri Dasar dan Kimia Tahun 2016 – 2017) - Alifiawan, Mukhammad Mabrur; Ramadhan, Ayu Mustikasari; Radianto, Denny Oktavina (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2019)
This research was conducted with the aim to determine the effect of variables including Return on Assets (ROA), Debt to Equity Ratio (DER), Earning per Share (EPS) and Exchange Rate on Stock Prices of Multinational Enterprises of Basic and Chemical Industries listed on the Exchange Indonesian Securities in the period of the year (2016 - 2017). The independent variables in this study are Return on Assets (ROA), Debt to Equity Ratio (DER), Earning per Share (EPS) and Exchange Value while the dependent variable is the Stock Price of Basic Industry and Chemical Industry Multinational Companies. Sampling in this study was conducted by random sampling method so as to produce 17 Basic Industry and Chemical Multinational Companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study used an analysis of the Normality Test, Correlation Test, F Test and T Test using SPSS. The results of the study are Return of Assets (ROA), Debt to Equity Ratio (DER), Earning per Share (EPS) and Exchange Rate overall effect on Stock Prices. Return of Assets (ROA) does not significantly influence stock prices, Debt to Equity Ratio (DER) does not significantly influence stock prices, Earning per Share (EPS) significantly influences stock prices, Exchange Rate does not significantly influence price stock.